Capturing landscape: phenomenological forays through art, atmospheres, and everyday life (Lebenswelt. Aesthetics and philosophy of experience., 2024)
This essay phenomenologically probes into the conceptual terrain encapsulating the notion of ‘landscape’. Drawing upon instances of artistic representations of landscapes, diverse facets of both actual and imaginary landscapes are delineated, encompassing cultural, chromatic, urban, and personal landscapes. It becomes evident that the apprehension of landscapes is intricately linked to the felt-bodily presence experienced within a specific locus. Thus, phenomenological and artistic methods based on the concept of atmosphere will become interesting for researching landscape. This is elucidated through empirical research approaches such as strollology, Aisthetic Fieldwork, and artistic research. The article thus underscores the relevance of employing these methodologies in the scholarly investigation of landscapes, shedding light on their potential to unveil nuanced dimensions of human engagement with the environment.